2019 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) 2019
DOI: 10.1109/i2mtc.2019.8826858
|View full text |Cite
|
Sign up to set email alerts
|

Towards end-to-end pulsed eddy current classification and regression with CNN

Abstract: Pulsed eddy current (PEC) is an effective electromagnetic non-destructive inspection (NDI) technique for metal materials, which has already been widely adopted in detecting cracking and corrosion in some multi-layer structures. Automatically inspecting the defects in these structures would be conducive to further analysis and treatment of them. In this paper, we propose an effective end-to-end model using convolutional neural networks (CNN) to learn effective features from PEC data. Specifically, we construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The trained CNN achieved a mean absolute error of 0.198 between the predicted profiles and ground truth. In terms of pulsed ECT, a multi-task CNN was developed in [25], which installed a softmax layer and a fully connection layer as two outputs in order to simultaneously classify the type and predict the depth of flaw, respectively. The total loss was an addition of the classification loss and regression loss.…”
Section: Introductionmentioning
confidence: 99%
“…The trained CNN achieved a mean absolute error of 0.198 between the predicted profiles and ground truth. In terms of pulsed ECT, a multi-task CNN was developed in [25], which installed a softmax layer and a fully connection layer as two outputs in order to simultaneously classify the type and predict the depth of flaw, respectively. The total loss was an addition of the classification loss and regression loss.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that deep CNNs have outstandingly succeeded in image classification and processing [31,35]. Moreover, deep CNNs that extract features hidden in data have potential for regression analysis [36][37][38][39]. CNN regression allows multiple outputs, relying on convolutional operations to train the corresponding weights.…”
Section: Introductionmentioning
confidence: 99%
“…Training samples were procured from a forward model with inputs and outputs exchanged. In terms of pulsed ECT, a multi-task CNN was developed in [13], which installed a softmax layer and a fully connection layer as two outputs in order to simultaneously classify the type and predict the depth of flaw, respectively. In [14], a plain CNN was used to estimate the crack depth for a heat transfer tube of the steam generator of a pressurised water reactor, which, compared to conventional numerical models, was less computationally expensive at inference time.…”
Section: Introductionmentioning
confidence: 99%